Usulan Peningkatan Kapasitas Produksi Bracket 78 Berdasarkan Waktu Siklus (PT XYZ) - Sugioko, Andre; Tanujaya, Andre (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2024)
PT XYZ is a manufacturing company engaged in producing dies and other components that go through the stamping part/press, welding, and fabrication processes. Currently, in carrying out production, the company has not been able to determine the target because there is no production capacity data, especially for the Bracket 78 component. The calculation of the bracket 78 product production capacity will use the Stopwatch Time Study to then produce the cycle time. The results of the measurement show a Bracket 78 product cycle time of 7.45 seconds. The cycle time will then be divided by the available time capacity. From this division, the Bracket 78 production capacity will be obtained at 3624 units per day. In this case, the company also wants to increase its production capacity to meet its long-term goal of becoming a Tier 1 supplier of PT Astra Honda Motor. Therefore, the improvement idea that can be given to the company to increase production capacity by utilizing the resources it has is to activate the machines and dies it has. Based on the calculation results, it can be proven that activating the machine at work station 2 can increase production capacity to 6102 units per day, or an increase of 68.37% compared to the production capacity before improvement.